Profit and Sustainability Perceptions Related to the Implementation of Blue Accounting in the Fishing Industry in Palabuhanratu - Moozanah, Siti; Rusdiansyah, Nurul; Rosyidah, Dania Meida; Riany, Meutia (Universitas Padjadjaran, 2024)
Blue Accounting integrates accounting principles with marine and coastal resource management to support sustainable development goals, focusing on the sea as its ecosystem. This study aims to understand perceptions of profit and sustainability related to the implementation of Blue Accounting in the fishing industry in Palabuhanratu. Additionally, it seeks to shift the common perception that accounting is solely about numbers. The qualitative approach used in this research is the social constructivism framework, often described as interpretivism. The results indicate that fishermen and boat owners have differing views on profit and sustainability concerning Blue Accounting implementation in Palabuhanratu’s fishing industry. The study addresses the problem statement by exploring these perceptions. Profit and sustainability are inseparable points in the implementation of Blue Accounting, generating various arguments and assumptions from different stakeholders who observe the level of awareness among port users in Palabuhanratu. This research highlights the importance of integrating sustainability into profit considerations within the fishing industry.